Effect of taurine in muscle damage markers and inflammatory cytokines in running exercise - Wang, Yucong; Xu, Tao; Zhao, Hui; Gu, Chunxiao; Li, Zhongzheng (Frontiers in Physiology, 2022)
The aim of this study was to investigate the effect of taurine on muscle damage markers and inflammatory markers in running. For that, ten healthy volunteers participated in this study (mean ± SEM; age 24 ± 1 yr, body mass 72.2±4.89 kg, height 174.03±2.85 cm, and BMI 23.83±1.27). The running exercise was performed for five kilometers, and blood was taken pre-exercise and pre-exercise+ tau and post-exercise and post-exercise +tau for biochemical assessment. We assessed serum creatine kinase (CK), CK isoenzyme, Lactate dehydrogenase (LDH), aspartate transaminase (AST), TNF-alpha, and IL-6. CK level was not significantly different both in the control and taurine administrated groups. However, creatine kinase isoenzyme was decreased (value) in the taurine administrated group when compared to the control group. AST was increased after the running in the control group, while it was decreased in the taurine administrated group. There was no significant difference observed in the LDH in both post-exercise and post-exercise +tau. TNF-alpha level was not also significantly different in both post-exercise and post-exercise +tau. However, IL-6 was decreased in the post-exercise +tau when compared to the post-exercise group. In conclusion, we observed that taurine decreases the inflammatory response by decreasing IL-6 and AST.